The Implementation of Central Bank Policy during the Economic Crisis in Lebanon (International Journal of Scientific Research and Management (IJSRM), 2024)
During the last four years Lebanon has been facing a severe crisis that have no way out. It has challenged all the potential of the authorities dealing with financial, social and economic sector circumstances. Recently this economic crisis is still going up in higher frequency and more effectively on the Lebanese people. During this crisis central bank of Lebanon implemented its own monetary policy that is represented by expansionary monetary policy. The aim of this paper is to detect the impact of central bank implemented monetary policy during the economic crisis in Lebanon using money supply and open market operations tools in both short and long run on coincident index and consumer price index. In this consideration we perform monthly data covering the period January 2017 to June 2022 by applying VAR model. The empirical results shows that money supply and open market operation have no impact on coincident index and consumer price index in the long run, in addition they do not cause them in the short run. However the impulse response function show some reactions of coincident index and consumer price index to shocks in money supply and open market operations.